2005
DOI: 10.1245/aso.2005.06.036
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical and Functional Outcome of Limb-Salvage Surgery With Vascular Reconstruction for Soft Tissue Sarcoma of the Extremity

Abstract: Vascular reconstruction is a feasible option in limb-salvage surgery for soft tissue sarcoma but is associated with an increased risk for postoperative complications, including amputation. Although function is not significantly worse after vascular reconstruction, the results are less predictable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 32 publications
4
75
2
1
Order By: Relevance
“…Our study reinforces previously reported findings of a smaller case-control study on 19 extremity sarcoma patients who underwent vascular reconstruction and were matched with 38 patients of similar age, tumor size, anatomic location, depth, and timing of radiotherapy, but without vascular involvement. 5 Although cases and controls in this previous study were not matched for the presence of synchronous metastases, when only M0 patients (n=40) were examined, the 5-year disease-free survival rates were similar at 83% and 74%. Our study corroborated this finding on a larger cohort of patients, with retroperitoneal and truncal in addition to extremity sarcomas as well as patients undergoing resection of both primary and recurrent disease.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our study reinforces previously reported findings of a smaller case-control study on 19 extremity sarcoma patients who underwent vascular reconstruction and were matched with 38 patients of similar age, tumor size, anatomic location, depth, and timing of radiotherapy, but without vascular involvement. 5 Although cases and controls in this previous study were not matched for the presence of synchronous metastases, when only M0 patients (n=40) were examined, the 5-year disease-free survival rates were similar at 83% and 74%. Our study corroborated this finding on a larger cohort of patients, with retroperitoneal and truncal in addition to extremity sarcomas as well as patients undergoing resection of both primary and recurrent disease.…”
Section: Discussionmentioning
confidence: 74%
“…Traditionally surgeons have been reluctant to perform major vascular resections for this disease, due to the inherently increased complexity of these operations and the uncertainty about the long-term oncologic benefit. Over the last decade, several case series have established the feasibility and safety of en bloc vascular resection for sarcomas of the extremity, [3][4][5][6][7] retroperitoneum, [8][9][10] or specifically the inferior vena cava (IVC). [11][12][13][14][15][16][17][18] What remains unknown is whether these complex procedures are associated with a durable prolongation of survival that justifies their morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial or arteriovenous reconstruction (autologous or synthetic graft) is conducted to maintain blood flow after en bloc resection. [22] When ipsilateral vena saphena magna, deep femoral vein junction and perigeniculate collaterals are protected, ligation of deep femoral vein does not cause any significant vascular complication. [23] In our study, in the patient who had SFT possessing malignant characteristics on anteromedial thigh (case 2), femoral artery and femoral vein resections were performed in order to make wide excision.…”
Section: Discussionmentioning
confidence: 99%
“…complications, deep venous thrombosis, and edema in the reconstruction group (45). These complications resulted in a higher risk of subsequent amputation, but functional results were excellent.…”
Section: Teaching Pointmentioning
confidence: 92%